The world of Gainsborough, 1727-1788 - Leonard, Jonathan Norton 1903-1975; Time-Life Books (Alexandria, Virginia Time-Life Books, 1979)
Life, times, and works of the 18th-century English painter.
An apprentice in rowdy London -- The country painter -- Fame in fashionable Bath -- Lords and lovely ladies -- Reynolds' Society of Artists -- Gainsborough's challenge -- London triumph -- Tribute from a rival.
Revised 1979.
Includes bibliographical references (page 187) and index.
Keywords: Gainsborough, Thomas -- 1727-1788.